The role of the ketogenic diet in the treatment of epilepsy - Karolina Kusiak; Anna Kuśnierz; Marta Głąbień; Daria Aleksandrowicz; Zofia Jakubczak; Paweł Miłkowski; Maria Weronika Zimniak; Aneta Kondratowicz; Olga Wieczorek; Patryk Śliwiak (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Epilepsy is a prevalent neurological condition that continues to pose therapeutic challenges. Despite the availability of various antiepileptic medications, up to one-third of patients still experience insufficient control of their seizures. One approach to managing epilepsy, particularly in drug-resistant cases, is the ketogenic diet. This diet, along with its variations, has shown effectiveness in reducing seizures across all age groups, with additional improvements in behavior. However, despite numerous studies, the exact mechanisms behind its therapeutic effects and potential risks to the body remain unclear. This review of the current literature outlines the fundamental principles and variations of the ketogenic diet, evaluates its safety and effectiveness in treating epilepsy, and explores the possible mechanisms underlying its success. Materials and methods: This article is based on the literature found in the PubMed database with the use of keywords like: "drug resistance epilepsy", "ketogenic diet", "epilepsy treatment". Conclusion: The ketogenic diet is an effective treatment for epilepsy, especially drug-resistant forms. It reduces the number of seizures and it also has a positive effect on patients' sleep and cognitive functions. Despite many years of using the diet and observing its effects we still do not fully understand its mechanisms of action.